EVALUATION OF FOUR FOREST SPECIES ASSOCIATED WITH COFFEE (Coffea Arabica L.) AND MONOCULTURE ON ECUADORIAN COAST - Suatunce Cunuhay, Pedro (2009)
An agroforestry system trial with coffee (Coffea arabica L.) was implanted in “La Represa” Farm, nearby Quevedo on 1997. Four forest species associated with coffee and it was also established plots of coffee and trees in monoculture systems, at the next plots. The forest species utilized were guayacán blanco (Cybistax donnell-smithii Rose), laurel prieto (Cordia megalantha Chadat), fernansánchez (Triplaris cumingiana Wedd) and teca (Tectona grandis L. F.). The intention was to compare the agroforestry systems and the monoculture system in both components trees and coffee. The production by hectare of coffee was major in monoculture system. The incidence (%) of mining of the coffee (Perileucoptera coffeella Green) was low in the two systems; also, there were no significant differences among both coffee plantation systems. The volume of the forest species was major in the agroforestry systems. According to the evaluation of the land efficiency usage, anyone of the agroforestry systems evaluated is better than the pure cultivations of these species.